Implementasi Fatwa Dsn No. 119 Tahun 2018 Tentang Pembiayaan Ultra Mikro di KSPPS BMT Bahtera Pekalongan - Fauziyah, Ike Nur; Fateh, Mohammad; Mardiyah, Dini (el hisbah Journal of Islamic Economic Law, 2021)
KSPPS BMT Bahtera Pekalongan is one of the Islamic Microfinance Institutions that is in great demand by the public. One product that is attractive and in great demand is ultra-micro financing, because this financing is affordable by the general public. The micro-ultra financing product contained in BMT Bahtera Pekalongan is interesting to study regarding whether this product is in accordance with the principles contained in the DSN Fatwa, considering that the DSN Fatwa is one of the legal bases that guides Islamic Financial Institutions in the operation of their products, therefore all products offered by Islamic Financial Institutions must adhere to the relevant DSN Fatwa. This research is an empirical legal research with qualitative descriptive data presentation. The results of the analysis show that the practice of ultra micro financing in KSPPS BMT Bahtera Pekalongan is in accordance with the provisions contained in the DSN-MUI Fatwa No. 119 of 2018 concerning ultra micro financing. The suitability of ultra-micro financing practices carried out by KSPPS BMT Bahtera Pekalongan is mandatory, because the DSN fatwa on ultra-micro financing is binding on Islamic financial institutions that have ultra-micro financing products, including KSPPS BMT Bahtera Pekalongan.